ANALISIS KEBIJAKAN PENDIDIKAN BERWAWASAN GENDER DI UNIVERSITAS NEGERI PADANG - Jabar, Maryati; Djamas, Djusmaini; Dj, Latisma (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2012)
This article is based on a research on Education Policy Analysis with GenderResponsive in Padang State University, with the purpose of examining gender profile ofstudents and lecturers; to reveal the problems of gender equity and equality; to find outfactors causing gender disparity; and to get solution for the problems. Data is analyzedusing Gender Analysis Pathway. This research recommends that Padang StateUniversity gradually apply the new paradigms of gender responsive for every policybased on university policy groundwork on gender responsive and INPRES No 9 year2000.Key words: responsiveness, gender in education, policy analysis